Mother tongue: Uncanny sound, migrant voice and the home movie. Issue 2 (1st August 2019) - Dwyer, Tessa
This article takes a personal journey through a home movie made by my immigrant grandfather. Constituting one of my grandfather's most complex narratives, the film Confidentially Yours provides a fascinating glimpse into 1950s Melbourne. It also holds deep significance for research into language and accent on-screen. Featuring my mother as narrator, the film is at once deeply familiar, homely and utterly strange – with my mother's voice almost unrecognizable due to her affected accent that harks back to a time when Britain's cultural influence in Australia was far more marked than today, with British Received Pronunciation (RP) speech dominating screen and broadcast media. Through the strange sound of my mother's voice-over in Confidentially Yours, this article reflects upon the significance of screen voice and accent more broadly in order to consider how tongue and tone address the viewer, perform the self and negotiate nation.